INVENTORY AND DISTRIBUTION OF MOLLUSC IN CORAL REEF OF BACAN ISLAND WATERS, NORTH MALUKU PROVINCE - Hendrik A.W. Cappenberg (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Bacan Island waters of North Maluku Province consisted of three main tropical ecosystems, namely mangrove, seagrass, and coral reef with the highest marine biodiversity. Mollusc is a group of marine fauna that most of them associated with coral reef. However, little is known about their information in the Bacan Island due to lack of study conducted there. The purpose of this study is to observe the diversity and distribution of mollusc fauna in the coral reef flat of Bacan Island. Mollusc inventory was done using Rapid Reef Resource Assessment (RRA) method by snorkling in the reefs of east coast (25 sites) and west coast (10 sites) of Bacan Island. The molluscs found were directly identified into species level and recorded. Results of inventory show that there are 47 species belong to 19 families with the family of Muricidae is the highest diversity (6 species), while the lowest are Buccinidae, Bursidae, Haliotidae, Olividae, Cardiidae, Isognomonidae and Spondylidae, respectively with only 1 species in each of those families. The highest species number of mollusc was distributed along the east coast of the island (40 species), and the lowest one was in the west coast (37 species). Some species such as Tridacna spp., Pinctada margaritifera and Pteria penguin are important species, because they have economical values. Keywords: biodiversity, molluscs, coral reef, Bacan Island, North Maluku